Trade and Competitiveness Between Turkey and the EU: Time Series Evidence - Utku Utkulu; Dilek Seymen (Turkish Economic Association, 2004)
The paper basically aims to clarify the level of price competitiveness of the Turkish firms towards the EU Single Market in aggregate level. Thus it naturally examines the demand for exports and imports for Turkey in relation to the EU. In order to model the trade between Turkey and the EU, we employ a time series analysis, namely cointegration method with error correction and causality mechanisms, for the period 1963-2002. The paper also deals with the possible effects of factors such as structural breaks, integration of markets, product innovation, supply, and omitted variables as regards the significance and the magnitude of the income and price elasticities. In the light of our empirical findings, some policy implications are drawn.
Keywords: F11; F13; F14; F15; 330; trade; competitiveness; income and price elasticities; EU; Turkey; time series modeling; cointegration